2020
DOI: 10.1097/wnr.0000000000001528
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor Val66Met polymorphism affects cortical thickness of rostral anterior cingulate in patients with major depressive disorder

Abstract: Objective The neuro-anatomical substrates of major depressive disorder (MDD) remain poorly understood. Brain-derived neurotrophic factor (BDNF) gene polymorphism (Val66Met/rs6265) is associated with neuro-plasticity and development. In the present study, we explore the influence of BDNF gene polymorphism on cortical thickness in nonelderly, first episode, drug-naive patients with MDD. Methods Two hundred and sixteen participants (105 MDD patients and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To test our hypotheses, the general linear model in SPSS was performed to analyze differences in subcortical volumes, with age, sex, education level, and ICV included as covariates. Multiple comparisons were corrected using the least significant difference method, and the significance threshold was set at P < 0.05 [37,38]. Two-tailed Pearson partial correlations were conducted to examine the relationships between abnormal subcortical volumes and clinical characteristics in the MD group, with age, sex, education level, and ICV controlled as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…To test our hypotheses, the general linear model in SPSS was performed to analyze differences in subcortical volumes, with age, sex, education level, and ICV included as covariates. Multiple comparisons were corrected using the least significant difference method, and the significance threshold was set at P < 0.05 [37,38]. Two-tailed Pearson partial correlations were conducted to examine the relationships between abnormal subcortical volumes and clinical characteristics in the MD group, with age, sex, education level, and ICV controlled as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical volume may also explain the genotype-related MEP changes that occur after NIBS. Neuroimaging studies reported that the cortical volume varied in some cortical regions between the genotype groups (Yang et al, 2012 ; Jasińska et al, 2017 ; Shen et al, 2020 ). When the interaction of cortical volume with the NIBS effect was considered, the volume of the sensorimotor cortex positively predicted the NIBS effect on MEP changes (Conde et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the interaction of cortical volume with the NIBS effect was considered, the volume of the sensorimotor cortex positively predicted the NIBS effect on MEP changes (Conde et al, 2012 ). However, this hypothesis lacks reliable information, because the different cortical volumes did not correspond to the same regions (Yang et al, 2012 ; Jasińska et al, 2017 ; Shen et al, 2020 ), and some studies failed to show the genotype-related cortical volume changes (Kim et al, 2015 ; McKay et al, 2019 ). Moreover, one study showed that the M1 volume in the Met/Met group was larger than that in the other groups (Jasińska et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Symptom severity and illness duration did not exhibit significant correlations with cortical thickness. These findings suggest that the presence of the Met allele may be a vulnerability factor for cortical thickness loss in the left rACC among MDD patients [ 76 ].…”
Section: Polymorphismmentioning
confidence: 99%
“…Additionally, the study demonstrated that among Val/Val individuals, the relationship between neglect and depression was mediated by emotion-focused coping styles and reduced perceived control, while this mediation was not observed in Met carriers [75]. Shen et al (2020) investigated the cortical thickness in MDD patients and found that individuals carrying the Met allele showed thinner cortical thickness in the left rostral anterior cingulate (rACC) compared to healthy controls carrying the same allele. Symptom severity and illness duration did not exhibit significant correlations with cortical thickness.…”
Section: Snp Rs6265 and Depressionmentioning
confidence: 99%